La felicidad y el sentido de la vida, según la mirada de jóvenes de distintos estratos sociales de Lima - Olortegui Saldaña, Alcibia Anamelva (2022)
This research aims to analyze the perceptions that young people in Lima attribute to happiness and the meaning of life. The qualitative approach and the phenomenological method allow the approach to the understanding of the meanings that the subjects give to their experiences. Through in-depth interviews, applied to 10 young people from different social strata of Lima, it was identified that they perceive that happiness is related to the meaning of life, and that they are seen as a dual and dynamic process that depends on the exercise of will of the same young people; it is a construction oriented to the future, but with present rewards. Also, factors have been identified, from their perception, critical for a happy life: the quality of the parent-child relationship, the choice and the study of a professional career product of their own choice. Due to the characteristics of the life cycle that young people go through, the importance of accompaniment spaces that contribute to the identification of emotional healing processes, product of their life stories, in order to strengthen the construction of their sense of life and of the experience of happiness in them.